Tinjauan Yuridis Kekuatan Informasi Elektronik DalamPembuktian Perkara Pencurian(Studi Putusan Kasus Nomor :62/ Pid.B/2013/PN.Kb.Mn di Pengadilan Negeri Kabupaten Madiun) - Pratama, Cahya Adi, Dr. Natangsa Surbakti, S.H., M.Hum (2017)
Development of science gives a significant impact in the field of criminal law. Therefore, understanding of limitative in Law No. 8 of 1981 on the Criminal Procedure Law may be narrow, because many new breakthroughs in the field of science and information technology, mobile phones, fax, video, internet, etc. Accordingly, the Law No. 11 Year 2008 on Information and Electronic Transactions give meaning extensions valid evidence under the applicable procedural law in Indonesia. This study was conducted to determine the use of Information and Electronic Based on the research result shows that the evidence is Information and Electronic Transactions "extension" of Article 184 of Law No. 8 of 1981 on the Criminal Procedure Law on valid evidence and the nature of the evidence is limitedly or limited to a specified course.